ANALISIS PERBEDAAN KADAR NITRIT SUMUR GALI TPA DENGAN PENAMBAHAN DAN TANPA Na2EDTA - Wiranatanegara, Yahya; Kurniawan, Ian; Mariadi, Pra Dian (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
The nitrite-in-water examination should be noted for the existence of the iron metal cation (Fe+), in the water cation samples can affect the test result of nitrite levels at the time of reading in the UV-Vis spectrophotometer. Na2EDTA Additions function to bind the metal found in the sample as well as chemical disorders as in the presence of chemical formation that can lead to not perfecting the association of substances to be analyzed so as to influence measurements at the time of reading in Spectrophotometer. The nitrite rate assessment was measured using the UV-Vis spectrophotometer method with a wavelength of 534 nm. The measuring rate range is 0.01 mg/L to 1.00 mg/L. There are differences in nitrite-level test results on well-dug water around the TPA with addition and without Na2EDTA using Uv-vis spectrophotometry.